PERKULIAHAN DARING : PEMBELAJARAN SENI BUDAYA DI TENGAH WABAH COVID-19 - Gita Kinanthi Purnama Asri (Universitas Achmad Yani Banjarmasin, 2020)
This paper is a response and an educational experience created to describe online lectures by involving creativity in learning cultural arts in the midst of the COVID-19 outbreak. Jargon at home has suddenly become popular since the outbreak of COVID-19 became a terror among Indonesian people. Government appeals to the community Work From Home (WFH), Study From Home (SFH) and Pray From Home (PFH) are serious matters that should be obeyed by the community. Since mid-March, teachers and students in the country have been collaborating with each other to conduct online lectures independently from their homes. Learning Cultural Arts as one of the compulsory subjects in the Elementary School Teacher Education Study Program (PGSD) at STKIP Banjarmasin, requires students to be smart in recognizing, understanding and mastering creative local culture based on local wisdom. The results of his study will be brought as basic skills in teaching arts and culture at elementary school level. Elementary art and culture learning is important to be implemented because it has a positive impact on the formation of learners' character, is multidimensional, multicultural and its content is unique that is not possessed by other subjects. This online lecture utilizes the rampant conditions of the COVID-19 epidemic by making learning products that are beneficial to society. This also helped the government in breaking the chain of COVID deployment19. Students use smartphones and existing applications such as KineMaster, Instagram, YouTube, Facebook, WhatsApp and others. The application functions as a production tool, product upload media, and product dissemination through social media. Here are some forms of online learning outcomes for art and culture learning; individual assignments make insta stories to write 100 words related to local cultural arts, make a 6-step video of the correct hand washing version of WHO, in the video students are required to search for and use elements of local cultural art in South Kalimantan such as the use of banjar songs as backsound, Banjar Language as the contents of oral texts, use of traditional clothing or Sasirangan nuances. Students are asked to make a stream related to the practice of various basic dances and folk songs. The activity of giving comments to each other is also carried out so that communication occurs interactively. Learning evaluation efforts are obtained by collecting tasks in a disciplined and neat manner, for example in accordance with task instructions and timely collection. Of course this is still far from the maximum, but this online learning should be continued in the future because there are still many things that can be explored by utilizing creativity and technological progress as an effort to deliver teaching materials.